(untitled)
The process of interpreting the Qur’an requires scientific tools to be able to reveal the meaning contained in each of its verses. One of the tools that must be owned and used is Arabic linguistics in accordance with the language used in the Qur’an. In a series of Qur’anic sentences there is the use of term which are mentioned explicitly sequentially, or mentioned implicitly using pronouns. Such sentence patterns are formulated in the rules of al-iz